Procédé Amélioré De Conservation Et De Stabilisation Du Fromage Peuhl Par L’effet Combiné Du Traitement Thermique Et Du Conditionnement Sous Vide - Joseph, Dossou; Karel, Montcho Jules; Serge, Londji; Laurent, Atchouké G. Donald; Sylvanus, Odjo (European Scientific Journal, ESJ, 2016)
This study focused on improving the conservation of traditional Fulani cheese (Wagashi) from Benin by using the combined effect of thermic dehydration and vacuum packaging. In order to increase the shelf life and cheese stability, some experiments were undertaken using heat treatment at 60 °C for 4 hours and vacuum packaging. The treated cheeses had a water content ranging from 32 to 35% and showed a reduced microbial load (102 CFU/g for the total aerobic mesophyl germs and 101 CFU/g for lactobacilli, yeasts and moulds. The cheeses nutritional and sensory quality was also preserved after treatment. Microbiological and physicochemical analyses carried out periodically on processed and stored cheeses in vacuum packaging showed these cheeses are stable for about 60 days, both under refrigeration (4-5 °C) and ambient temperature (28-32 °C). These results were confirmed by sensory analyses. However, over a two month’s period, the panelists preferred white cheeses than red colored cheeses stored under vacuum. The economic analysis performed on the mini-factory basis with a cheese processing capacity of 12000 liters milk per year, showed that heat treated cheese stored in vacuum packaging costs 55.35 FCFA a piece of 50 g (net weight) with a selling price of 150 FCFA giving a net profit of 63.1% and break-even point by 54.15 kg of cheese production.